Navigating the Challenges and Vagaries of Attaining Professional Status and Recognition for the UK Security Sector and Those Employed in It – A Worthwhile Pursuit or Potential Ephemerality? - Evanson, Garry (Digital Repository of Theses - SSBM Geneva, 2025)
The concept of a profession in the UK has been characterised by historical underpinning and strong cultural components, perhaps more so than elsewhere in the world, making for complexity and some lack of definitive understanding. Many in society and business are aware of the prestige and status that membership of an established profession brings, including the likelihood of potential power and financial reward, especially when fully recognised by the State institutions. Security in UK is not generally considered a profession despite moves by much of the sector in that direction, marked by the inception of chartered status in 2011 and increasing access to university degrees in various security disciplines. The research aimed to evaluate the challenges facing the UK security sector in attaining formal professional status and assess whether it is needed, if routes exist now, or what they might be in the future, and whether alternatives may be more advisable. The research met this aim by evaluating qualitatively and with informal mixed methodology the current state of the professional concept and its relationship with security. The primary research was based on cross sectional surveys and interviews of different security populations using thematic and content analysis to interpret participant views as well as to provide a comparison with the secondary research based on a literature review. The evidence suggests that rather than pursuing a traditional UK professional model it would be beneficial to adopt a neo-expert framework but one that is embedded within a concept similar to UK Engineering which contains all regulatory controls for standards and codified ethics and provides established career paths present in the more traditional constructs. This approach if strategised correctly by a unified sector leadership and based on inextricable linkage to governmental oversight would indeed improve individual and collective status and provide the elevated recognition sought. This could eventually extend to society more generally if focus and attention are provided to that. The research will prove important to all those in the sector who have an interest in security status, influence, recognition and their positioning in business or society, or just in security more generally. The study outlines and recommends a possible future with a sector initiative to achieve professional recognition. Additionally, the findings help contextualise some ideas surrounding the sector’s professional positioning in relation to regulation, standards, and socio-ethical accountability alongside identifying the feasibility of professional attainment or the adoption of alternative frameworks and approaches.